Kontrol Gender Dalam Fenomena Overachievement Mahasiswa di Universitas Negeri Jakarta: Studi Atas Pola Ekspektasi dan Pengawasan Sosial Berbasis Gender - Hisyam, Ciek Julyati; Tuffahati, Fadia; Rahma, Intan Aulia; Fakhria, Itsna; Safaatun, Muharomah Ayu; Al-Fauziah, Rohmatul Amaliyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine how gender control operates within the phenomenon of overachievement among students at Universitas Negeri Jakarta. Overachievement is understood as a response to social expectations that demand students to excel academically, engage in organizational activities, and build a strong personal brand. Using a qualitative approach and case study method, this research explores the lived experiences of two students of different genders, Fatimah and Sufyan, to understand how gendered social expectations and surveillance influence the way they navigate overachievement. The findings reveal that female students tend to experience greater social pressure and must manage their performance and self-image in line with dominant gender norms. In contrast, male students are afforded more freedom to succeed without the same image constraints. These findings are analyzed using feminist theory, particularly the concepts of gender performativity and symbolic control, which show that gender-based power relations continue to shape student experiences in the urban academic sphere.